2022
DOI: 10.31234/osf.io/jkvyd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cortical haemodynamic responses predict individual ability to recognise vocal emotions with uninformative pitch cues but do not distinguish different emotions

Abstract: We investigated the cortical representation of emotional prosody in normal-hearing listeners using functional near-infrared spectroscopy and behavourial assessments. Consistent with previous reports, listeners relied most heavily on F0 cues when recognizing emotion cues; performance was relatively poor—and highly variable between listeners—when only intensity and speech-rate cues were available. Using functional near-infrared spectroscopy (fNIRS) to image cortical activity to speech utterances containing natur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…For preregistered exploratory analyses, we also derived HbO–HbR difference values by subtracting HbR from HbO estimates per participant, ROI and block type. This difference measure is commonly employed in fNIRS studies addressing clinical questions [103,104] and has recently been shown to be useful in answering questions in cognitive neuroscience [105,106]. The HbO–HbR difference offers three main advantages when communicating and interpreting changes in cortical oxygenation measured with fNIRS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For preregistered exploratory analyses, we also derived HbO–HbR difference values by subtracting HbR from HbO estimates per participant, ROI and block type. This difference measure is commonly employed in fNIRS studies addressing clinical questions [103,104] and has recently been shown to be useful in answering questions in cognitive neuroscience [105,106]. The HbO–HbR difference offers three main advantages when communicating and interpreting changes in cortical oxygenation measured with fNIRS.…”
Section: Methodsmentioning
confidence: 99%
“…Third, the relationship between HbO and HbR estimates can be used to categorize responses very conservatively as systemic phenomena (blood pressure changes) or true cortical responses. Here, negatively correlated HbO–HbR pairs are more likely to represent cortical activation [107], while positively correlated pairs are more likely to represent physiological confounding phenomena such as blood pressure changes, muscle oxygenation or extracerebral changes [108,109], and the latter can easily be excluded for more conservative analyses [105,106]. We present results from preregistered exploratory models fitted to negatively correlated HbO–HbR pairs here, and models fitted to all HbO–HbR pairs in electronic supplementary material, (S5).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, each HbO–HbR difference value can be categorised by the relationship between the original estimates: Taking a conservative stance, positively correlated HbO–HbR pairs may result from systemic phenomena such as blood‐pressure or extracerebral changes (Yücel et al, 2021; Zimeo Morais et al, 2017), whereas negatively correlated HbO–HbR pairs are more likely to reflect true cortical activation (Wolf et al, 2002). By retaining HbO–HbR values from negatively‐correlated pairs only, one can take a conservative approach to analyses (Moffat et al, 2023; Moffat, Caruana, & Cross, 2024). We present results from models fit to negatively correlated HbO–HbR pairs below and models fit to HbO and HbR values simultaneously, and to all HbO–HbR difference values (positively and negatively correlated) in Supplementary Materials A (Figure S2).…”
Section: Methodsmentioning
confidence: 99%
“…For exploratory analyses, we also derived HbO-HbR difference values by subtracting HbR from HbO estimates per participant, ROI, and block type. This difference measure is commonly employed in fNIRS studies addressing clinical questions (e.g., Kaynezhad et al, 2019;Kolyva et al, 2014) and has recently been shown to be useful in answering questions in cognitive neuroscience (e.g., Moffat et al, 2022). The HbO-HbR difference offers three main advantages when communicating and interpreting changes in cortical oxygenation measured with fNIRS.…”
Section: Haemodynamic Response Amplitude: First Levelmentioning
confidence: 99%
“…Second, the sign (+/-) of an HbO-HbR difference value is informative: positive difference values correspond to canonical haemodynamic responses, while negative values respond to inverted responses (also called negative BOLD responses). Third, the relationship between HbO and HbR estimates can be used to categorise responses very conservatively as systemic phenomena (blood-pressure changes) or true cortical responsesnegatively-correlated HbO-HbR pairs are more likely to represent cortical activation (Wolf et al, 2002), while positively-correlated pairs are more likely to represent physiological confounding phenomena such as blood pressure changes, muscle oxygenation or extracerebral changes (Yücel et al, 2021;Zimeo Morais et al, 2017), and can easily be excluded for more conservative analyses (e.g., Moffat et al, 2022). We present results from exploratory models fit to negatively-correlated HbO-HbR pairs here, and models fit to all HbO-HbR pairs in Supplementary Materials (S5).…”
Section: Haemodynamic Response Amplitude: First Levelmentioning
confidence: 99%